Postoperative pain management in gynecologic laparoscopic surgeries - Nurul Amin, Mohammad; Bhattacharjee, Ramanuj; Ferdouse Lisa, Shahreen; Akhter, Sunzida (International Journal of Research in Medical Sciences, 2024)
Background: Postoperative pain management is crucial in gynecologic laparoscopic surgeries, as inadequate pain relief can delay recovery and affect patient satisfaction. This study evaluated the effectiveness of different postoperative pain management strategies in a cohort of female patients undergoing elective procedures. The primary objective was to assess the effectiveness of multimodal analgesia, including nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, and regional anesthesia, on postoperative pain relief. Secondary objectives included evaluating side effects associated with these pain management strategies. Methods: This cross-sectional observational study was conducted from July 2022 to June 2024 at the department of anesthesia, in different private clinics in Sylhet region, Bangladesh. A total of 60 adult female patients aged 18 to 65 years undergoing elective gynecologic laparoscopic surgeries were included. Data were collected using patient interviews and medical records, assessing pain levels using the visual analog scale (VAS) at 1, 6, 12, and 24 hours postoperatively. Statistical analysis was performed using SPSS software. Results: Among the 60 participants, the mean age was 35 years, with 55% undergoing laparoscopic hysterectomy and 45% laparoscopic cystectomy. At 1 hour postoperatively, the mean VAS score was 6.5±1.2, decreasing significantly to 2.2±0.9 by 24 hours (p<0.01). Pain management strategies included NSAIDs in 75% of patients, opioids in 50%, and regional anesthesia in 41.7%. The incidence of adverse effects varied: nausea was reported in 33.3% of opioid users compared to only 6.7% in NSAID users. Conclusions: The findings indicate that implementing multimodal analgesia, particularly incorporating regional anesthesia, can enhance postoperative pain management in gynecologic laparoscopic surgeries. This approach not only improves pain relief but also minimizes the adverse effects commonly associated with opioid use.